Cortical thickness and volume abnormalities in Internet gaming disorder: Evidence from comparison of recreational Internet game users. (29th June 2018) - Wang, Ziliang; Wu, Lingdan; Yuan, Kai; Hu, Yanbo; Zheng, Hui; Du, Xiaoxia; Dong, Guangheng
Abstract: Although online gaming may lead to Internet gaming disorder (IGD), most players are recreational game users (RGUs) who do not develop IGD. Thus far, little is known about brain structural abnormalities in IGD subjects relative to RGUs. The inclusion of RGUs as a control group could minimize the potential effects of gaming experience and gaming‐related cue familiarity on the neural mechanism of IGD subjects. In this study, structural magnetic resonance imaging data were acquired from 38 IGD subjects and 66 RGUs with comparable age, gender, and educational level. Group differences in cortical thickness and volume were analyzed using the FreeSurfer software. Correlations between cortical changes and addiction severity were calculated for both groups. Compared with the RGU group, the IGD group showed significantly decreased cortical thickness in the left lateral orbitofrontal cortex, inferior parietal lobule, bilateral cuneus, precentral gyrus, and right middle temporal gyrus. Moreover, significantly reduced cortical volume was observed in the left superior temporal gyrus and right supramarginal gyrus in the IGD group. Whole‐brain correlational analysis indicated different correlations between the two groups. The brain regions that showed group differences were considered to be involved in cognitive control, decision making, and reward/loss processing. These functions may serve as potential mechanisms that explain why IGD individuals experience negative outcomes in frequent game playing. Abstract : Compared with recreational game users, Internet gaming disorder (IGD) subjects showed significantly decreased cortical thickness in the left lateral orbitofrontal cortex, bilateral cuneus along with the right middle temporal gyrus. Moreover, significantly reduced cortical volume was observed in the left superior temporal gyrus in IGD subjects. The changed brain regions were thought to be involved in cognitive control, decision making, and reward/loss processing which might provide evidence for the negative influence that IGD could bring.